CFD Study of the Hydrodynamics of Slug Flow Systems: Interaction between Consecutive Taylor Bubbles - J. D. P. Araújo (2015)
Slug flow is one of the most frequently occurring multiphase flow patterns in industrial processes. A deep knowledge of its fundamentals is necessary to accurately model not only the fluid flow but also reaction and heat and mass transfer in several operation units. A numerical study is reported on the dynamics of slug flow, under laminar regime, in vertical columns of stagnant and co-current Newtonian and non-Newtonian liquids (shear-thickening and shear-thinning). A CFD package (Ansys FLUENT) with the VOF methodology was applied to simulate the flow of individual and pairs of consecutive Taylor bubbles. The behaviour of the most relevant hydrodynamic features with the approach of the trailing bubble towards the leading one is addressed, with particular emphasis to the role of the liquid rheology and flow configuration. The main results presented are the velocity ratio curves between consecutive bubbles, the variation of the bubbles shape, and the axial velocity and viscosity fields in the surrounding liquid. This bubble-bubble interaction data can be a keystone to improve and complement continuous slug flow simulators used for very long columns.